Chemical fingerprint database of bioaerosols - Garcia Alcega, Sonia; Coulon, Frederic; Tyrrel, Sean (Cranfield University, 2017)
The impact of emissions from urban, agricultural and industrial scenarios on local air quality is of growing policy concern. Deleterious health effects can arise following exposure to infective microbes and the exposure risk to bioaerosols are difficult to quantify in real time. Current monitoring methods are labour intensive and a standardised protocol does not exist yet. Additionally, capturing sufficient amounts of material to generate distinguishable and reproducible patterns for bioaerosols identification and classification is still difficult. To overcome the inherent limitations of culturing, chemical fingerprint analysis of microbial biomarkers such as phospholipid fatty acids (PLFAs) and microbial volatile organic compounds (MVOCs) is proposed. Different air samples collection devices are currently being tested (Coriolis, Tenax® cartridges and polycarbonate filters) and each method will be evaluated depending on the complexity of the sampling, laboratory procedure, compounds identified and the limit of detection of the equipment.
Keywords: Bioaerosols'; 'Atmospheric Aerosols'; 'Environmental Monitoring'; 'Environmental Science'